Avaliação do conhecimento dos cirurgiões-dentistas sobre as condutas adotadas frente a traumatismos alveolodentários - Azevedo, Renato Azevedo de (2012)
The accurate diagnosis of dental trauma, together with the choice of adequate procedure is fundamental for a favorable prognosis to the traumatized patient. Although there are several studies evaluating dentist knowledge facing dental trauma, there are only three studies carried out in Brazil. The aim of this study was to evaluate through a specific survey the knowledge of dentists on dental trauma in Pelotas city regarding their conduct facing some dental trauma injuries. In addition, this study intended to correlate the outcome with the time since the dentist graduation, his/her specialization level, workplace and gender. A survey with five sociodemographic questions and five specific questions on knowledge about dental trauma was carried out. The survey was applied to professionals by 45 first year dental students from the Federal University of Pelotas in the second semester of 2011. The data was submitted to descriptive statistical analysis and this association was tested by Chi-square test (p≥0.05).The response rate was 68%. There was a higher number of dentists with up to 10 years since graduation (45.4%) who worked in private dental office (66.1%) and with some specialization (63.7%). Only the variable related to years since graduation was associated to the outcome (P=0.0004). It can concluded that the knowledge of the dentists related to dento-alveolar trauma is less since the passing years after graduation pass because it seems there are no familiarity with current treatment guidelines.Other independent variables such as gender, workplace and level of post-graduation were not associated to the number of correct answers. Continuing education courses should be offered to the dentists by educational institutions, in order to keep these professionals updated regarding management of dento-alveolar trauma injuries